Highly regioselective isomerizing hydroformylation of long-chain internal olefins catalyzed by a rhodium bis(phosphite) complex - Pandey, Swechchha; Chikkali, Samir H. (ChemCatChem, 2015)
The single-step synthesis, coordination behavior, and application of a bis(phosphite) ligand in the isomerizing hydroformylation of internal olefins was investigated. Interestingly, high-pressure NMR spectroscopy investigations revealed unexpected inequivalency of the two phosphorus nuclei, which display bisequatorial coordination of the bis(phosphite) ligand in a trigonal bipyramidal rhodium complex. Upon employment in the isomerizing hydroformylation of the exceedingly challenging plant oil derived substrate methyl oleate, the bis(phosphite) rhodium complex revealed an unprecedented linear selectivity of 75%.
Keywords: alkenes; bis(phosphite)s; Hydroformylation; isomerization; Rhodium